The effect of different ground characteristic to the similarity and stability of target spectra in FSR micro-sensor network / Arifah Aziela Jamaludin - Jamaludin, Arifah Aziela (2012)
This paper investigates the effect of different ground characteristic to the target spectra for the performance evaluation of ground base forward scattering radar (FSR) micro-sensor network based on the simulation model. The obtained results show the stability and similarity of target spectra when the conductivity and permittivity of different ground exists. This analysis result gives the idea of which kind database should the system has and at the same time can reduce the misclassification in the FSR micro-sensor network system.